2016
DOI: 10.1136/bjophthalmol-2016-309219
|View full text |Cite
|
Sign up to set email alerts
|

Topical 1% 5-fluoruracil as a sole treatment of corneoconjunctival ocular surface squamous neoplasia: long-term study

Abstract: AimsTo report long-term clinical outcome of topical 1% 5-fluoruracil (5-FU) as a sole treatment of ocular surface squamous neoplasia (OSSN).Methods41 patients affected by OSSN were included. Each patient underwent full ophthalmological examination at baseline, with cytological or histological confirmation. Patients were treated by topical chemotherapy with 1% 5-FU four times a day for 4 weeks. One course was defined as 4 weeks of topical chemotherapy. Adjunctive courses were administered after 1 month of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 25 publications
1
48
0
1
Order By: Relevance
“…This study found that sub-clinical OSSN was detected by HR-OCT in 17% of patients whose tumors were noted to have resolved clinically. While the clinical implications of sub-clinical disease are unknown, OSSN recurrences are noted in 0-28% of eyes treated with 5-FU and in 4-20% of eyes treated with IFN [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It can be postulated that recurrences may be driving residual disease or sub-clinical disease, especially since most occurred within the first year after stopping treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that sub-clinical OSSN was detected by HR-OCT in 17% of patients whose tumors were noted to have resolved clinically. While the clinical implications of sub-clinical disease are unknown, OSSN recurrences are noted in 0-28% of eyes treated with 5-FU and in 4-20% of eyes treated with IFN [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It can be postulated that recurrences may be driving residual disease or sub-clinical disease, especially since most occurred within the first year after stopping treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive pathological assessment consisting of impression or scrape cytology can identify the dysplastic epithelial cells characteristic of OSSN [7,[34][35][36]. Some features on impression cytology are suggestive of invasive disease, such as the presence of syncytial sheaths, macronucleoli and inflammatory cells [7,21]. But these features are not diagnostic of invasive disease and further investigations are required if they are present.…”
Section: Management Issuesmentioning
confidence: 99%
“…Topical MMC 0.04% is the preferred chemotherapeutic agent as SCC does not seem to respond to topical IFNa 2b [18]. Similarly, although it may regress in 50% of patients treated with topical 5-FU, it recurs in 75% of these [21]. By contrast, Shields et al reported a prospective series of patients with conjunctival SCC who demonstrated excellent response to topical MMC 0.04% [23].…”
Section: Management Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Átlagosan másfél ciklust követően a betegek 83%-ánál alakult ki teljes rezolúció. Joag nemrégiben megjelent közleményében 44 pácienst kezeltek naponta 4 × 1 1%-os 5-FU-szemcseppel, amely során egy ciklusban a páciens egy hétig csepegtetett, majd három hétig nem használt 5-FU-t. Átlagosan négy ciklust követően az esetek 82%-ában alakult ki teljes rezolúció, a recidívaráta egy év után 6%, két év után pedig 15% volt [50].…”
Section: -Fuunclassified